The Influence of Digital Marketing, Product Value, and Green Innovation on The Development of Craft SMEs - Aktris Monika Favorit Makbul; Erika Nurmartiani; Y Ony Djogo; Taufik Zulfikar; Vip Paramarta (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2025)
This research aims to determine the influence of digital marketing, product value and green innovation on the development of SMEs in West Lombok Regency gacor5000. The research method used is a quantitative method with an exploratory approach. The data used in this research consists of primary data obtained through a questionnaire distributed online using Google Form, as well as secondary data obtained from the West Lombok Regency Cooperatives and UKM Service. The population in this research is all craft SMEs in West Lombok Regency that have been operating for at least one year and have marketing activities, both conventional and digital. The research sample was determined using a saturated sampling technique, where all members of the population of 113 SMEs were taken as samples. The data analysis technique used in this research is multiple linear regression analysis with the help of statistical software. The partial analysis results show that digital marketing, product value and green innovation have a significant influence on the development of SMEs in West Lombok Regency. The results of the F test show that simultaneously, the three independent variables have a significant effect on the dependent variable, namely the development of SMEs. It is hoped that the results of this research will provide insight for SMEs in optimizing digital marketing strategies, increasing product value, and implementing green innovation to strengthen the competitiveness of their businesses. Apart from that, this research can also be a reference for local governments in designing policies that support the growth of the SME sector in the region. Keyword: Digital Marketing, Product Value, Green Innovation, SME Development, West Lombok.